2005
DOI: 10.1385/ct:5:3:269
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin Cardiac Dysfunction: Effects on Calcium Regulatory Proteins, Sarcoplasmic Reticulum, and Triiodothyronine

Abstract: Utilizing a model of chronic doxorubicin cardiomyopathy, this study examines the relationship between changes in expression and function of calcium handling proteins and contractile dysfunction. A possible mechanism to account for this relationship is suggested. New Zealand white rabbits were injected with either doxorubicin (1 mg/kg, twice weekly for 8 wk) or 0.9% NaCl. Gene transcript, protein levels, and the function of several proteins from the left ventricle were assessed. Protein levels of sarcoplasmic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 40 publications
13
36
0
Order By: Relevance
“…Furthermore, doxorubicin reduced NCX1 expression (Fig. 4D), in agreement with previous findings showing similar effects in atrial and ventricular preparations isolated from doxorubicin-treated rabbits (Olson et al, 2005) and in dog heart sarcolemmal vesicles (Caroni et al, 1981). Collectively, the reduction in SERCA2 and NCX1 expression can explain the elevated diastolic [Ca 2ϩ ] i and the slowing of [Ca 2ϩ ] i relaxation kinetics, as well as reduced rate of myocyte relaxation caused by doxorubicin.…”
Section: Tvp1022 Attenuated the Deleterious Effects Of Doxorubicin Onsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, doxorubicin reduced NCX1 expression (Fig. 4D), in agreement with previous findings showing similar effects in atrial and ventricular preparations isolated from doxorubicin-treated rabbits (Olson et al, 2005) and in dog heart sarcolemmal vesicles (Caroni et al, 1981). Collectively, the reduction in SERCA2 and NCX1 expression can explain the elevated diastolic [Ca 2ϩ ] i and the slowing of [Ca 2ϩ ] i relaxation kinetics, as well as reduced rate of myocyte relaxation caused by doxorubicin.…”
Section: Tvp1022 Attenuated the Deleterious Effects Of Doxorubicin Onsupporting
confidence: 91%
“…Doxorubicin decreased the expression of SERCA2 and NCX1, but did not affect the expression of RyR, calsequestrin, or phospholamban. Accordingly, previous studies showed that doxorubicin decreased SERCA2 mRNA and protein expression in cultured NRVM (Arai et al, 2000), adult rat ventricular cardiomyocytes (Timolati et al, 2006), and rabbit in vivo model of doxorubicin cardiotoxicity (Arai et al, 1998;Olson et al, 2005). Furthermore, doxorubicin reduced NCX1 expression (Fig.…”
Section: Tvp1022 Attenuated the Deleterious Effects Of Doxorubicin Onmentioning
confidence: 77%
“…DOX has been consistently found to decrease SERCA2a mRNA and protein levels (Arai et al, 1998;Olson et al, 2005;Richard et al, 2011), and SERCA2a impairment is closely associated with decreased heart contractility in DOX cardiotoxicity (Frank et al, 2003;Periasamy & Huke, 2001). In this study, DOX treatment caused significant decrease (p50.05) of SERCA2a mRNA expression level in the DOX only-treated group which can partially explain the rise of cytosolic and mitochondrial calcium levels.…”
Section: Discussionsupporting
confidence: 52%
“…Several studies have proved that reactive oxygen species resulted from DOX treatment has either direct or indirect effect to calcium regulatory proteins (Arai et al, 1998;Olson et al, 2005;Richard et al, 2011). Arai et al (2000) demonstrated the effect of DOX to the expression and activity of SERCA2a, a calcium pump responsible for calcium influx from cytosol to sarcoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 99%
“…3f,g). SERCA-2a is a molecular target in DOX toxicity 45 . DOX (1 mM) caused an increase in t (that is, slower Ca 2 þ reuptake), which was reversed by adenoviral transduction of ILK WT (Fig.…”
Section: Resultsmentioning
confidence: 99%